2011
DOI: 10.1007/s13224-011-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery Doppler indices better predictor for fetal outcome in IUGR

Abstract: :Objective(s) : To compare the role of middle cerebral artery and umbilical artery Doppler pulsatility indices in predicting the fetal outcome in intrauterine growth restriction. Method(s) : The prospective study was conducted on 121 subjects. They were divided into two groups. The study group (n=71) consists of high risk group of pregnant women with growth restricted fetuses. The control group (n=50) consists of pregnant women with healthy fetuses. Both the groups were evaluated by middle cerebral artery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…9.37 days (p-value<0.05). Our findings are in accordance with the study of Hemlata D et al [1] in which neonates with abnormal MCA Doppler were more than twice is likely to be admitted in neonatal intensive care unit that the neonates with normal Doppler waveforms.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…9.37 days (p-value<0.05). Our findings are in accordance with the study of Hemlata D et al [1] in which neonates with abnormal MCA Doppler were more than twice is likely to be admitted in neonatal intensive care unit that the neonates with normal Doppler waveforms.…”
Section: Resultssupporting
confidence: 93%
“…Umbilical artery and middle cerebral artery are the most frequently studied vessels and are good predictor of growth restricted fetuses at risk of antenatal compromise [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar design, Dhand et al [5] observed a sensitivity and specificity of 44 and 61.5 %, respectively, in prediction of the IUGR outcome. The positive and negative predictive values in their study were in 83 and 20 %, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Nalini Y et al found that 35%cases with abnormal Umbilical artery and Middle cerebral artery Doppler waveforms required NICU admission. 12,13 Changes in MCA-PI were not as consistent as those of MCA-PSV. MCA-PI was normal in 5 patients with abnormal PSV which finally had adverse perinatal outcome.…”
Section: Discussionmentioning
confidence: 66%